2020
DOI: 10.2478/asn-2020-0017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of phenolic contents and antioxidant activities of some medicinal plants growing in Algerian Aurès Mountains

Abstract: The objective of this study is to evaluate the antioxidant activities of six medicinal plants growing in Algerian Aurès Mountains. Total phenolic and flavonoids contents were measured using colorimetric methods, and the antioxidant capacities were evaluated using the DPPH radical scavenging and β-carotene bleaching tests. Juniperus phoenica L. had significantly the higher total phenolic compounds (53.6±3.86 mg GAE.g−1 DM) (p<0.05); followed by Romarinus officinalis L. (26.1±3.15 mg GAE.g−1 DM) and Artemisia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…TPCs values were 8.64 and 20.53 mg GAE/g dry material, while TFCs values were 5.47 and 11.11 mg QE/g dry material, respectively for A. herba-alba and A. campestris. On the other hand, the extracts showed DPPH scavenging activities with EC 50 values of 33.71 and 2.47 μg/mL, respectively for A. herba-alba and A. campestris31 . Megdiche-Ksouri et al(2015) reported that the methanolic and ethyl acetate extracts of Tunisian A. campestris demonstrated high DPPH antioxidant scavenging activity with IC 50 values of 6.0 and 10.0 μg/mL, respectively)…”
mentioning
confidence: 93%
“…TPCs values were 8.64 and 20.53 mg GAE/g dry material, while TFCs values were 5.47 and 11.11 mg QE/g dry material, respectively for A. herba-alba and A. campestris. On the other hand, the extracts showed DPPH scavenging activities with EC 50 values of 33.71 and 2.47 μg/mL, respectively for A. herba-alba and A. campestris31 . Megdiche-Ksouri et al(2015) reported that the methanolic and ethyl acetate extracts of Tunisian A. campestris demonstrated high DPPH antioxidant scavenging activity with IC 50 values of 6.0 and 10.0 μg/mL, respectively)…”
mentioning
confidence: 93%
“…For instance, using the CUPRAC assay, the chloroform extract was the most effective while the n–BuOH extract was the most active using the FTC assay. In another work, the aqueous extract of leaves of Algerian T. algeriensis was active only using ABTS (IC 50 = 52 ± 31 μ g/mL) while the ethanolic extract was active using both the DPPH and ABTS assays with IC 50 ( μ g/mL) of 52 ± 4 and 42 ± 0.99, respectively [ 45 ]. In contrast, Ziani et al showed that both aqueous and hydroethanolic extracts exhibit antioxidant activities using DPPH, RP, β –carotene bleaching, and TBARS assays, with a high efficiency of the hydroethanolic fraction except when using β –carotene bleaching in which the aqueous extract demonstrated the highest activity [ 7 ].…”
Section: In Vitro Pharmacological Propertiesmentioning
confidence: 99%
“…Anti-inflammatory effects of T. algeriensis in different doses were evaluated by utilizing different animal models representing various changes associated with inflammation, namely, carrageenan-induced paw oedema, total leukocyte count in paw fluid, and acetic acid-induced vascular permeability. In the study by El Ouahdani et al [ 63 ], the effect was evaluated in vivo in a carrageenan-induced hind paw oedema model. This assay has been increasingly used to test new anti-inflammatory drugs.…”
Section: Thymus Algeriensis Boiss and Reutmentioning
confidence: 99%
“…However, when mixed with A. herba-alba oil in the same quantity, the oedema inhibition was better (89.99 ± 4.08%). Similarly, for Diclofenac, a maximum inhibition (88.57 ± 0.81%) under the same conditions and at the sixth hour after carrageenan injection [ 63 ].…”
Section: Thymus Algeriensis Boiss and Reutmentioning
confidence: 99%
See 1 more Smart Citation